2007
DOI: 10.4049/jimmunol.178.11.7283
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Enhances Immunity to Streptococcus pneumoniae by Targeting Uptake to FcγR on Dendritic Cells

Abstract: C-reactive protein (CRP) is an acute phase reactant with roles in innate host defense, clearance of damaged cells, and regulation of the inflammatory response. These activities of CRP depend on ligand recognition, complement activation, and binding to FcγR. CRP binds to phosphocholine in the Streptococcus pneumoniae cell wall and provides innate defense against pneumococcal infection. These studies examine the effect of this early innate defense molecule on the development of Abs and protective immunity to S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 59 publications
2
33
0
2
Order By: Relevance
“…These reports suggest that these pentraxin proteins behave like antibodies recognizing foreign antigens on pathogens and directing them to cells of the innate immune system [16]. In support of this idea, it was also found that Fcγ receptor uptake of CRP-opsonized Streptococcus pneumoniae increased the immune response against these bacteria [95]. Moreover, CRP also seems to have an anti-inflammatory effect mediated by Fcγ receptors.…”
Section: New Ligands For Fcγ Receptorssupporting
confidence: 65%
See 1 more Smart Citation
“…These reports suggest that these pentraxin proteins behave like antibodies recognizing foreign antigens on pathogens and directing them to cells of the innate immune system [16]. In support of this idea, it was also found that Fcγ receptor uptake of CRP-opsonized Streptococcus pneumoniae increased the immune response against these bacteria [95]. Moreover, CRP also seems to have an anti-inflammatory effect mediated by Fcγ receptors.…”
Section: New Ligands For Fcγ Receptorssupporting
confidence: 65%
“…Two members of the pentraxin superfamily [91], which are multimeric cyclic proteins, are reported to bind human and mouse Fcγ receptors. These pentraxins are C-reactive protein (CRP) and serum amyloid P (SAP) [92][93][94][95]. These proteins are usually not found in serum of healthy individuals, but they are rapidly expressed in large amounts during inflammation and microbial infections.…”
Section: New Ligands For Fcγ Receptorsmentioning
confidence: 99%
“…CRP has been shown to enhance uptake and presentation of pneumococcal antigens through Fc␥R on dendritic cells in vitro (43). However, we did not characterize mutant CRP for binding to Fc␥R because Fc␥R do not participate in CRP-mediated protection of mice against pneumococcal infection (44).…”
Section: Discussionmentioning
confidence: 99%
“…CRP was found to bind to a ligand on Leishmania donovani and phosphorylcholine-expressing Neisseria meningitides, and hence increase their uptake by human phagocytes (Culley et al, 1996, Casey et al, 2008. Thomas-Rudolph et al (2007) have also reported that innate recognition by CRP enhances effective uptake and presentation of bacterial antigens through Fc-gamma receptors on dendritic cells and stimulates protective adaptive immunity. CRP has been shown to express multiple antiinflammatory effects on neutrophils.…”
Section: In Vitromentioning
confidence: 99%